High-nitrogen-doped layered porous waxberry kernel-based activated carbon as well as preparation method and application thereof

Through bayberry core raw materials and collaborative nitrogen doping technology, high-nitrogen doping layered porous activated carbon was prepared, which solved the shortcomings of biomass activated carbon in pore structure and adsorption effect, achieved efficient adsorption of organic steam in CO2 atmosphere, and improved the Purification effect.

CN119191288APending Publication Date: 2024-12-27ZHEJIANG UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411281306.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing biomass activated carbon has difficulty in regulating the pore structure, specific surface area and chemical properties, and insufficient types and quantities of surface functional groups, resulting in poor adsorption effect, especially in the process of CO2 utilization and storage, which is not good in the purification effect of volatile organic compounds.

Method used

Using bayberry core as raw material, pretreatment of nitric acid solution, synergistically doping nitrogen and KHCO3 of urea and ammonia as activator, two-step ammonia nitrogen doping treatment was carried out to prepare high-nitrogen doping layered porous activated carbon to form a rich micro/ Mesoporous structure and high nitrogen doping.

Benefits of technology

It significantly improves the specific surface area, developed pore structure and high nitrogen doping amount of activated carbon, enhances its adsorption ability and hydrophilic properties, and is suitable for the separation of organic steam in CO2 atmosphere, and improves the adsorption efficiency of ketones and aldehyde compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191288A_ABST
    Figure CN119191288A_ABST
Patent Text Reader

Abstract

The invention discloses high-nitrogen-doped layered porous waxberry kernel-based activated carbon and a preparation method and application thereof.The preparation method of the activated carbon comprises the steps that waxberry kernels are washed with water, dried, crushed into particles, screened, soaked in a nitric acid solution for pretreatment, washed and dried to obtain a pre-oxidized precursor, then the pre-oxidized precursor is mixed with a nitrogen source and a potassium activating agent, and the high-nitrogen-doped layered porous waxberry kernel-based activated carbon is obtained. The preparation method comprises the following steps: firstly, preparing a one-step impregnated nitrogen-doped carbon precursor, heating, stirring and drying in deionized water to obtain the one-step impregnated nitrogen-doped carbon precursor, then calcining and activating in a mixed atmosphere of nitrogen and ammonia gas, finally soaking in a hydrochloric acid solution, washing, filtering, drying and screening to obtain the final finished product nitrogen-doped layered porous activated carbon. According to the activated carbon, the waxberry kernels serve as raw materials, urea and ammonia gas serve as nitrogen sources, KHCO3 serves as an activating agent, the activated carbon is heated, stirred and reacted in water and then calcined and activated, high-temperature activation and synergistic nitrogen doping are achieved, and compared with a traditional nitrogen doping mode, the activated carbon is higher in nitrogen doping rate, richer in specific surface area and pore structure and obvious in performance advantage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmental protection and new energy material preparation, and specifically relates to a high-nitrogen-doped layered porous bayberry core-based activated carbon and a preparation method and application thereof. Background Art

[0002] Carbon Capture, Utilization and Storage (CCUS) adds a carbon utilization process to the Carbon Capture and Storage (CCS) technology. That is, the captured CO2 is purified and put into a new production process for recycling, turning CO2 into a resource and extending the carbon industry chain. It can not only achieve carbon emission reductions, but also generate economic benefits, so it is more realistic and operational.

[0003] There are four main ways to efficiently utilize CO2. First, it can be used to prepare chemical products and carbon-based materials with high added value, such as bulk inorganic products such as soda ash and baking soda, as well as urea, salicylic acid, synthesis gas, various organic compound monomers and polymers; second, it can be used as a gas fertilizer to increase crop photosynthesis rate to increase crop yields, or it can be used by microalgae to convert into liquid fuels, biofertilizers, etc.; third, it can be used to mineralize CO2 and co-produce chemical products using bulk solid waste rich in calcium and magnesium (such as steelmaking waste, cement kiln dust, fly ash, phosphogypsum, etc.); fourth, it can be injected into geological bodies to seal or enhance the exploitation of petroleum and shale oil.

[0004] However, the utilization and storage of CO2 have requirements for the quality of CO2. If volatile organic compounds are mixed in CO2, it will not only affect the quality of chemical products and reduce the efficiency of microalgae carbon fixation technology, CO2 gas fertilizer technology, etc., but may also cause serious damage to the geological and deep-sea storage environment. Therefore, before CO2 is utilized and stored, the remaining volatile organic compounds must be purified. Using activated carbon prepared from biomass as raw material to purify VOCs has always been considered a suitable method with low cost and high efficiency.

[0005] During the thermochemical conversion of biomass, unstable carbon is converted into aromatic carbon skeletons and stored in some carriers, forming a renewable environmentally friendly material with fine texture structure - biomass activated carbon. The raw materials of biomass activated carbon are widely available and the preparation conditions are mild. Agricultural waste such as corn stalks, banana peels, fruit cores, animal feces such as cow dung, pig dung and domestic garbage can all be used as raw materials for biomass activated carbon. With its economy and environmental friendliness, biomass activated carbon is considered to be a low-cost alternative to activated carbon. Biomass activated carbon obtained only after preliminary carbonization has the following problems: ① The pore structure, specific surface area and chemical properties are difficult to control; ② The types and number of surface functional groups are small and most of them are negatively charged functional groups, which have poor adsorption effect on anions; ③ The surface is highly hydrophobic, the number of specific active sites is limited, and the specific capacitance and catalytic performance are low. In order to meet specific requirements, biomass activated carbon usually needs to be modified to improve its defects.

[0006] Heteroatom doping and activation processes can expand the pore structure of pure biochar, increase its specific surface area and active sites, and improve the oxygen reduction reaction activity, catalytic performance and electrochemical performance of biochar. Among the many hybrid elements (N, B, S, P, O), N and C are in adjacent positions in the periodic table and have similar atomic radii, so it is easier to replace C atoms to form N-containing functional groups. In addition, the incorporation of highly electronegative N atoms will produce a dipole moment, enhance the interaction between adjacent positively charged C atoms and external substances, and thus significantly improve the polarity, alkalinity and catalytic performance of biochar. Therefore, the N-doped modified biochar not only has a highly porous structure, a large specific surface area and strong intermolecular forces, but also has strong surface activity and electrochemical properties, showing strong ion exchange capacity, pH buffering capacity and adsorption capacity, and has broad application prospects in soil remediation, VOCs adsorption, sewage treatment, electrochemical energy storage, catalysis and other aspects.

[0007] According to the different methods of introducing N elements, the preparation methods are mainly divided into in-situ synthesis method and post-treatment method. The in-situ synthesis method is to introduce N source during the carbonization process. The N atoms introduced by this method are evenly distributed in the C skeleton, with good doping effect and high N content. The N form in the prepared carbon material mainly exists in a relatively stable structural nitrogen form, but there are problems such as single pore structure, underdeveloped structure, limited specific surface area, corrosive activator, and environmental pollution. The post-treatment method refers to the preparation of carbon materials first, and then the modified activated carbon is treated with N-containing compounds to obtain nitrogen-doped activated carbon. The nitrogen-doped activated carbon prepared by this method has a high N doping amount and is simple to operate, but there are problems such as uneven N doping and a small number of nitrogen-containing functional groups. Different preparation methods have different advantages and limitations. In order to achieve better results, it is often necessary to use multiple methods in combination. Therefore, it is of great practical value to provide a method for preparing activated carbon that can maintain a large specific surface area, a developed pore structure, and can contain rich heteroatom functional groups. Summary of the invention

[0008] In view of the above-mentioned technical problems existing in the prior art, the purpose of this application is to provide a high-nitrogen-doped layered porous bayberry core-based activated carbon and its preparation method and application. The present invention utilizes bayberry core to prepare a layered porous activated carbon with a large specific surface area, developed micro / mesopores and a high nitrogen doping content.

[0009] The technical solution adopted by the present invention is as follows:

[0010] A method for preparing highly nitrogen-doped layered porous bayberry core-based activated carbon comprises the following steps:

[0011] 1) Washing the raw material bayberry core with water to remove surface dust, drying, crushing into particles, sieving, soaking in nitric acid solution for pretreatment, and then washing and drying to obtain a pre-oxidation precursor;

[0012] 2) mixing the pre-oxidized precursor, nitrogen source and potassium activator in step 1), adding and immersing in deionized water, stirring under heating conditions to make the raw materials mixed evenly and react completely, and then drying in a forced air drying oven to obtain a one-step impregnation nitrogen-doped carbon precursor;

[0013] 3) placing the nitrogen-doped carbon precursor impregnated in step 2) in a tubular furnace for two-step ammonia nitrogen doping, and calcining and activating in a mixed atmosphere of nitrogen and ammonia to obtain nitrogen-doped layered porous activated carbon;

[0014] 4) Finally, the product is immersed in a hydrochloric acid solution, washed, filtered, dried, and sieved to obtain the final nitrogen-doped layered porous activated carbon.

[0015] Furthermore, in step 1), the conditions for the first drying treatment are: drying in a 105°C forced air drying oven for 8 hours; and the conditions for the second drying treatment are: drying in a 105°C forced air drying oven for 24 hours.

[0016] Furthermore, in step 1), the mesh size of the sieving is 30-60 meshes, the concentration of the nitric acid solution is 0.5-2M, stirring treatment is also performed during the soaking pretreatment, the treatment temperature is 80-100°C, and the treatment time is 3-6h.

[0017] Furthermore, in step 1), the filtrate is washed until the conductivity is lower than 20 μS / cm.

[0018] Furthermore, in step 2), the nitrogen source is urea, and the mass ratio of the pre-oxidation precursor to the nitrogen source is 1.0:1.0-3.0.

[0019] Furthermore, in step 2), the heating temperature is 70-100° C., and the stirring reaction time is 4-6 h.

[0020] Furthermore, in step 2), the solid-liquid ratio of the pre-oxidation precursor to deionized water is 1 g: 200-400 mL, preferably 1 g: 250-300 mL.

[0021] Further, in step 2), the potassium activator is one or both of KOH and KHCO3, preferably KHCO3. KOH is used as an activator, and the activation degree is high, but KOH is corrosive and will corrode the equipment, and the residual KOH will pollute the environment. The present invention further preferably uses KHCO3 with milder chemical properties and lower cost.

[0022] Furthermore, the mass ratio of the pre-oxidation precursor to the potassium activator is 1.0:0.5-3.0. In the present invention, KHCO3 as an activator can corrode macropores into micropores. Too little use leads to incomplete activation, and too much use will block the pores. The present invention further preferably has a mass ratio of the pre-oxidation precursor to the potassium activator of 1.0:1.5-2.0.

[0023] Furthermore, in step 3), the volume fraction of ammonia in the mixed atmosphere of nitrogen and ammonia is 30-70%, the calcination activation temperature is 600-1000° C., and the activation time is 2-4 h, preferably 2-3 h.

[0024] Furthermore, in step 3) during the calcination activation, nitrogen is first introduced, and when the temperature reaches the target temperature, a mixture of nitrogen and ammonia is introduced, the activation ends the cooling process, and only nitrogen is introduced.

[0025] Furthermore, in step 4), the concentration of the hydrochloric acid solution is 0.5-2M, stirring is performed during immersion, the immersion time is 20-60 minutes, and then the filtrate is washed with deionized water until the filtrate is neutral.

[0026] The high-nitrogen-doped layered porous bayberry core-based activated carbon described in the present invention can be well used for adsorbing and separating organic vapors in a CO2 atmosphere, wherein the organic vapors are one or more of ketones, aldehydes or acid compounds, preferably one or more of acetone, C1-C4 alkyl aldehydes (such as formaldehyde or acetaldehyde, etc.), C1-C4 alkyl acids (such as formic acid or acetic acid, etc.).

[0027] The high-nitrogen-doped layered porous bayberry core-based activated carbon of the present invention uses bayberry core as raw material, adopts urea and ammonia as nitrogen sources, and KHCO3 as an activator. It is heated and stirred in water before calcination and activation is carried out to achieve high-temperature activation and synergistic nitrogen doping. Compared with traditional nitrogen doping methods, the nitrogen doping rate is higher, the specific surface area and pore structure are richer, and the performance advantages are obvious.

[0028] Compared with the prior art, the present invention has the following main advantages:

[0029] (1) The highly nitrogen-doped layered porous bayberry core-based activated carbon prepared by the present invention uses cheap, readily available, non-toxic and harmless discarded bayberry core as a carbon source, with a wide source of raw materials and low cost; and uses KHCO3 with milder chemical properties as an activator;

[0030] (2) The highly nitrogen-doped layered porous bayberry core-based activated carbon prepared by the present invention has a greatly improved nitrogen doping amount after two-step in-situ synergistic nitrogen doping. It has rich nitrogen-containing functional groups, developed micro / mesoporous structure, large specific surface area and strong intermolecular forces, which enhances its hydrophilicity, improves the alkalinity of the material surface, and provides a large number of chemically active sites, which is conducive to adsorption at room temperature or low temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1a This is the nitrogen isothermal adsorption-desorption curve of the highly nitrogen-doped layered porous bayberry core-based activated carbon in Example 1.

[0032] Figure 1b This is the pore size distribution diagram of the highly nitrogen-doped layered porous bayberry core-based activated carbon in Example 1.

[0033] Figure 2a This is the nitrogen isothermal adsorption-desorption curve of the highly nitrogen-doped layered porous bayberry core-based activated carbon in Example 3.

[0034] Figure 2b This is the pore size distribution diagram of the highly nitrogen-doped layered porous bayberry core-based activated carbon in Example 3.

[0035] Figure 3aThis is the nitrogen isothermal adsorption-desorption curve of the highly nitrogen-doped layered porous bayberry core-based activated carbon in Example 5.

[0036] Figure 3b This is the pore size distribution diagram of the highly nitrogen-doped layered porous bayberry core-based activated carbon in Example 5.

[0037] Figure 4a This is a scanning electron microscope image of the highly nitrogen-doped layered porous bayberry core-based activated carbon in Example 2.

[0038] Figure 4b This is a scanning electron microscope image of the highly nitrogen-doped layered porous bayberry core-based activated carbon in Example 3.

[0039] Figure 4c This is a scanning electron microscope image of the highly nitrogen-doped layered porous bayberry core-based activated carbon in Example 4. DETAILED DESCRIPTION

[0040] The present invention is further described below with reference to examples and drawings. These examples are merely descriptions of the implementation modes of the present invention, but are not limited to the contents described below.

[0041] Embodiment 1:

[0042] (1) 10.000 g of raw bayberry kernels were cleaned with tap water and deionized water respectively to remove surface dust, and dried in a 105° C. forced air drying oven for 8 h. The dried bayberry kernels were crushed with a crusher, and sieved to obtain bayberry kernel particles of 30-60 mesh. The bayberry kernel particles were soaked in a nitric acid solution with a concentration of 1 M and a temperature of 80-100° C. for 4 h, with magnetic stirring during the soaking. The bayberry kernel particles were then taken out, washed with deionized water until the conductivity of the filtrate was less than 20 μS / cm, and dried in a 105° C. forced air drying oven for 24 h to obtain a pre-oxidation precursor.

[0043] (2) 1.000g of pre-oxidized precursor, 1.000g of KHCO3 and 1.000g of urea were mixed and dissolved in 300ml of deionized water, and magnetically stirred at 90℃±5℃ for 4h to make the mixture uniform and react completely. After the solution was evaporated to dryness, the mixture was placed in a 105℃ forced air drying oven for 12h to obtain a one-step impregnation nitrogen-doped carbon precursor; the one-step impregnation nitrogen-doped carbon precursor was placed in a tubular furnace for two-step ammonia nitrogen doping, and the temperature was raised to 700℃ at a rate of 5℃ / min under a nitrogen atmosphere (nitrogen flow rate of 100ml / min), and then the atmosphere was changed to a mixed atmosphere of nitrogen and ammonia (ammonia flow rate of 30ml / min, nitrogen flow rate of 70ml / min), and the temperature was kept for activation for 2h. After the activation was completed, the atmosphere was changed to a nitrogen atmosphere (nitrogen flow rate of 100ml / min), and after cooling to room temperature, the activated nitrogen-doped layered porous activated carbon was obtained.

[0044] (3) The activated nitrogen-doped layered porous activated carbon was immersed in a 1 M hydrochloric acid solution with magnetic stirring for 30 min, then washed with deionized water until the filtrate was neutral, and dried in a forced air drying oven at 105 °C for 24 h. The activated carbon with a mesh size of 30-60 was sieved to obtain the final product of biomass nitrogen-doped layered porous activated carbon, which was recorded as HNBC-1.

[0045] The prepared activated carbon was used to adsorb acetone vapor in a CO2 atmosphere. The adsorption conditions were: the acetone vapor was diluted with CO2, the inlet concentration of acetone was 500 ppm, the total gas flow rate was 100 ml / min, the amount of activated carbon used was 0.2000 g, the adsorption temperature was 25 ± 3 °C, and the adsorption amount of acetone vapor by activated carbon is shown in Table 1.

[0046] Embodiment 2:

[0047] Example 2 Preparation of activated carbon The steps of Example 1 were repeated, except that the following conditions were changed in step (2):

[0048] 1) The amount of KHCO3 was replaced with 2.000 g.

[0049] 2) The heating and stirring temperature changes from 90℃±5℃ to 75℃±5℃, and the stirring time changes to 6h.

[0050] 3) The activation temperature was changed from 700°C to 800°C under the mixed atmosphere of nitrogen and ammonia, and the other conditions remained unchanged. The final product of biomass nitrogen-doped layered porous activated carbon was denoted as HNBC-2.

[0051] The prepared activated carbon was used to adsorb acetone vapor in a CO2 atmosphere. The adsorption conditions were repeated in Example 1. The adsorption amount is shown in Table 1.

[0052] Embodiment 3:

[0053] Example 3 Preparation of activated carbon The steps of Example 1 were repeated, except that the following conditions were changed in step (2):

[0054] 1) The amount of KHCO3 was replaced with 2.000 g, and the amount of urea was replaced with 2.000 g.

[0055] 2) The heating and stirring temperature changes from 90℃±5℃ to 75℃±5℃, and the stirring time changes to 6h.

[0056] 3) The activation temperature was changed from 700°C to 800°C under a mixed atmosphere of nitrogen and ammonia, and the flow rates of ammonia and nitrogen were changed to 50 ml / min and 50 ml / min, respectively. The other conditions remained unchanged, and the final product of biomass nitrogen-doped layered porous activated carbon was denoted as HNBC-3.

[0057] The prepared activated carbon was used to adsorb acetone vapor in a CO2 atmosphere. The adsorption conditions were repeated in Example 1. The adsorption amount is shown in Table 1.

[0058] Embodiment 4:

[0059] Example 4 Preparation of activated carbon The steps of Example 1 were repeated, except that the following conditions were changed in step (2):

[0060] 1) The amount of KHCO3 was replaced with 2.000 g, and the amount of urea was replaced with 2.000 g.

[0061] 2) The heating and stirring temperature changes from 90℃±5℃ to 75℃±5℃, and the stirring time changes to 6h.

[0062] 3) The activation temperature under the mixed atmosphere of nitrogen and ammonia was changed from 700°C to 800°C, the flow rates of ammonia and nitrogen were changed to 50 ml / min for ammonia and 50 ml / min for nitrogen, the activation time was changed to 3 h, and the other conditions remained unchanged. The final product of biomass nitrogen-doped layered porous activated carbon was recorded as HNBC-4.

[0063] The prepared activated carbon was used to adsorb acetone vapor in a CO2 atmosphere. The adsorption conditions were repeated in Example 1. The adsorption amount is shown in Table 1.

[0064] The activated carbon HNBC-4 prepared in Example 4 was used to adsorb toluene vapor in a CO2 atmosphere. The adsorption conditions were: toluene vapor was diluted with CO2, the inlet concentration of toluene was 500 ppm, the total gas flow rate was 100 ml / min, the amount of activated carbon used was 0.2000 g, the adsorption temperature was 25±3°C, and the adsorption amount of activated carbon to toluene vapor was 211.215 mg / g.

[0065] It can be seen that the adsorption capacity of the activated carbon of the present application for acetone is significantly better than that for toluene.

[0066] Embodiment 5:

[0067] Example 5 Preparation of activated carbon The steps of Example 1 were repeated, except that the following conditions were changed in step (2):

[0068] 1) The amount of KHCO3 was replaced with 2.000 g, and the amount of urea was replaced with 3.000 g.

[0069] 2) The heating and stirring temperature changes from 90℃±5℃ to 75℃±5℃, and the stirring time changes to 6h.

[0070] 3) The activation temperature under the mixed atmosphere of nitrogen and ammonia was changed from 700°C to 1000°C, the flow rates of ammonia and nitrogen were changed to 70 ml / min, 30 ml / min, and the activation time was changed to 3 h. The other conditions remained unchanged. The final product of biomass nitrogen-doped layered porous activated carbon was denoted as HNBC-5.

[0071] The prepared activated carbon was used to adsorb acetone vapor in a CO2 atmosphere. The adsorption conditions were repeated in Example 1. The adsorption amount is shown in Table 1.

[0072] Embodiment 6:

[0073] The preparation steps of activated carbon in Example 6 were repeated in Example 4, with the only difference being that the following conditions were changed in step (2): the nitrogen source was replaced by melamine, and the other conditions remained unchanged. The final product of biomass nitrogen-doped layered porous activated carbon was denoted as HNBC-6.

[0074] The prepared activated carbon was used to adsorb acetone vapor in CO2 atmosphere, and the adsorption amount is shown in Table 1.

[0075] Embodiment 7:

[0076] The preparation steps of activated carbon in Example 7 were repeated in Example 4, except that the following conditions were changed in step (2): the activator was replaced by zinc chloride of equal mass from KHCO3, and the other conditions remained unchanged. The final product of biomass nitrogen-doped layered porous activated carbon was denoted as HNBC-7.

[0077] The prepared activated carbon was used to adsorb acetone vapor in a CO2 atmosphere. The adsorption conditions were repeated in Example 1. The adsorption amount is shown in Table 1.

[0078] Embodiment 8:

[0079] The preparation steps of activated carbon in Example 8 are repeated in Example 4, with the only difference being that the following conditions are changed in step (1): the carbon source is replaced by pine wood of equal mass instead of bayberry kernel, and the other conditions remain unchanged. The final product of biomass nitrogen-doped layered porous activated carbon is denoted as HNBC-8.

[0080] The prepared activated carbon was used to adsorb acetone vapor in a CO2 atmosphere. The adsorption conditions were repeated in Example 1. The adsorption amount is shown in Table 1.

[0081] Embodiment 9:

[0082] The preparation steps of activated carbon in Example 9 are repeated in Example 4, except that the following conditions are changed in step (2): the activation atmosphere is pure nitrogen, the gas flow rate is 100 ml / min, and the other conditions remain unchanged. The final product of biomass nitrogen-doped layered porous activated carbon is denoted as HNBC-7.

[0083] The prepared activated carbon was used to adsorb acetone vapor in a CO2 atmosphere. The adsorption conditions were repeated in Example 1. The adsorption amount is shown in Table 1.

[0084] Figure 1a , Figure 2a and Figure 3a The nitrogen isothermal adsorption-desorption curves of HNBC-1, HNBC-3 and HNBC-5 prepared in Examples 1, 3 and 5 are shown in FIG. Figure 1b , Figure 2b and Figure 3b The pore size distribution diagrams of HNBC-1, HNBC-3 and HNBC-5 prepared in Examples 1, 3 and 5 are shown respectively. Figure 1a-3a As shown in the figure, the shapes of the adsorption-desorption isotherms of the three activated carbons are very similar, similar to Type I in the IUPAC classification. In the low-pressure adsorption region, the adsorption amount increases rapidly, which is mainly due to the rapid filling effect of the microporous structure of the four activated carbon materials. As the adsorption pressure continues to increase, the micropore filling effect gradually ends, causing the adsorption curve to reach the platform area. In this area, as the relative pressure continues to increase, the adsorption curve changes gently and the adsorption amount increases less. This type I adsorption isotherm indicates that the three activated carbons contain more micropores. At the same time, the nitrogen adsorption-desorption curves of the three activated carbons all have a relatively obvious hysteresis loop structure, which is caused by the capillary condensation phenomenon, indicating that in addition to the microporous structure on the activated carbon, there is also a relatively obvious mesoporous structure, and based on the shape of the hysteresis loop, it can be inferred that the mesopores on the four activated carbons are slit-type channel structures.

[0085] Figure 1b-3b The pore size distribution diagram shows that the three activated carbons all contain abundant micropores (<2nm), a small amount of mesopores (2-50nm), and almost no macropores (>50nm). The well-developed pore structures of the three activated carbons are consistent with the inferred results of their type I adsorption isotherms. Although the microporosity of HNBC-5 is lower than that of HNBC-3, the specific surface area of ​​HNBC-5 is much larger than that of HNBC-3, which may be the reason why the N2 adsorption capacity of HNBC-5 is higher than that of HNBC-3.

[0086] Figure 4a , Figure 4b and Figure 4cThese are the SEM images of HNBC-2, HNBC-3, and HNBC-4. By comparison, it can be seen that after being magnified by 10.00KX, the surface of HNBC-2 is relatively uniform and flat, with clearly visible holes; the surface of HNBC-3 is relatively rough and disordered, with many small holes in addition to clearly visible holes; and the surface of HNBC-4 has many protrusions, with stronger disorder and porosity, denser pore distribution, and extends into the tissue. It can be inferred that the specific surface area and micropore volume of HNBC-4 are larger than those of HNBC-2 and HNBC-3, which is consistent with the BET test results of the three activated carbons.

[0087] The activated carbon materials prepared in Examples 1-9 were subjected to nitrogen isothermal adsorption and desorption tests, and the calculated BET results and the results obtained from the element content test are shown in Table 1.

[0088] Table 1 Specific surface area, element content and acetone adsorption of activated carbon samples

[0089]

[0090] The pore structure related parameters and elemental analysis data of the nitrogen-doped activated carbon prepared in Examples 1-9 are shown in Table 1.

[0091] The following conclusions can be drawn from the experimental results in Table 1:

[0092] 1) By comparing Example 1 and Example 2, it can be seen that increasing the amount of activator, extending the impregnation time of the carbon source, activator and nitrogen source, and increasing the activation temperature will increase the specific surface area, total pore volume, micropore internal surface area and micropore volume of the activated carbon, but will reduce the nitrogen doping rate, which is not conducive to the adsorption of acetone vapor in the CO2 atmosphere by the activated carbon.

[0093] 2) By comparing Example 2 and Example 3, it can be seen that increasing the amount of the modifier nitrogen source and increasing the ammonia flow rate will increase the nitrogen doping rate.

[0094] 3) By comparing Example 3 and Example 4, it can be seen that extending the activation time of the precursor under the mixed atmosphere will reduce the nitrogen doping rate of the activated carbon, which is not conducive to the adsorption of acetone vapor in CO2 by the activated carbon, but will increase the specific surface area, total pore volume, micropore internal surface area and micropore volume of the activated carbon.

[0095] 4) By comparing Example 4 and Example 5, it can be seen that increasing the amount of the modifier nitrogen source and increasing the ammonia flow rate will increase the nitrogen doping rate, which is beneficial to the adsorption of acetone vapor in the CO2 atmosphere by the activated carbon, but the activation temperature is too high, which affects the pore-forming process and reduces the specific surface area, total pore volume, micropore internal surface area and micropore volume of the activated carbon.

[0096] 5) By comparing Example 4 and Example 6, it can be seen that the activated carbon prepared with melamine as the nitrogen source is lower in specific surface area and pore structure than the activated carbon prepared with urea as the nitrogen source, and the nitrogen doping rate is reduced, which is not conducive to the adsorption of acetone vapor in CO2 atmosphere by the activated carbon. Compared with melamine, urea as a nitrogen source can better induce nitrogen doping, and at the same time, oxygen-containing functional groups can be better retained at a higher doping dose, so that the adsorption performance of the activated carbon is further improved.

[0097] 6) By comparing Example 4 and Example 7, it can be seen that changing the type of activator will reduce the specific surface area, total pore volume, micropore internal surface area and micropore volume of the activated carbon, resulting in a decrease in the nitrogen doping rate, which is not conducive to the adsorption of acetone vapor in the CO2 atmosphere. Zinc chloride is an excellent activator. The temperature and dosage will greatly affect its activation effect. It is generally suitable for 400-600°C. The temperature of the calcination activation in the mixed atmosphere of nitrogen and ammonia in the embodiment of the present invention is above 700°C, which may be the reason for its lower performance.

[0098] 7) By comparing Example 4 and Example 8, it can be seen that the activated carbon prepared with pine wood as the carbon source is inferior to the activated carbon prepared with bayberry kernel as the carbon source in terms of specific surface area, total pore volume, pore structure and nitrogen content, and its adsorption capacity of acetone vapor in CO2 atmosphere is also relatively low.

[0099] 8) By comparing Example 4 and Example 9, it can be seen that the activated carbon prepared under pure nitrogen activation atmosphere is significantly lower in specific surface area, total pore volume, micropore inner surface area and micropore volume than the activated carbon prepared under a mixed atmosphere of ammonia and nitrogen. The lack of ammonia as both a nitrogen source and an activator leads to a decrease in the nitrogen doping rate of the activated carbon, and its adsorption of acetone in a CO2 atmosphere is also significantly reduced.

[0100] The invention uses bayberry kernels as a carbon source, and the prepared activated carbon has a high adsorption capacity for acetone vapor, achieving good technical effects. In addition, China is a major country for bayberry planting and consumption, with bayberry planting area accounting for more than 90% of the global bayberry planting area, so a large amount of discarded bayberry kernels are generated every year, and the bayberry kernel has a high lignin content, so the yield of preparing activated carbon is relatively high.

[0101] According to the above description, those skilled in the art to which the present invention belongs can also change and modify the above implementation method. Therefore, the implementation method of the present invention is not limited by the above embodiment, and any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing highly nitrogen-doped layered porous bayberry core-based activated carbon, characterized in that The following steps are involved: 1) The raw material bayberry core is washed with water to remove surface dust, dried, crushed into particles, sieved, soaked in nitric acid solution for pretreatment, and then washed and dried to obtain a pre-oxidation precursor; 2) mixing the pre-oxidized precursor, nitrogen source and potassium activator in step 1), adding and immersing in deionized water, stirring under heating conditions to make the raw materials mixed evenly and react completely, and drying to obtain a one-step impregnation nitrogen-doped carbon precursor; 3) placing the nitrogen-doped carbon precursor impregnated in step 2) in a tubular furnace for two-step ammonia nitrogen doping, and calcining and activating in a mixed atmosphere of nitrogen and ammonia to obtain nitrogen-doped hierarchical porous activated carbon; 4) Finally, the product is soaked in hydrochloric acid solution, washed, filtered, dried and sieved to obtain the final nitrogen-doped layered porous activated carbon.

2. The method for preparing a highly nitrogen-doped layered porous bayberry core-based activated carbon according to claim 1, characterized in that In step 1), the mesh size of the sieving is 30-60 meshes, the concentration of the nitric acid solution is 0.5-2M, stirring treatment is also performed during the soaking pretreatment, the treatment temperature is 80-100°C, and the treatment time is 3-6 hours.

3. The method for preparing a highly nitrogen-doped layered porous bayberry core-based activated carbon according to claim 1, characterized in that In step 1), washing is performed until the conductivity of the filtrate is lower than 20 μS / cm.

4. The method for preparing a highly nitrogen-doped layered porous bayberry core-based activated carbon according to claim 1, characterized in that In step 2), the nitrogen source is urea, the mass ratio of the pre-oxidation precursor to the nitrogen source is 1.0:1.0-3.0, and the mass ratio of the pre-oxidation precursor to the potassium activator is 1.0:0.5-3.0, preferably 1.0:1.5-2.

0.

5. The method for preparing a highly nitrogen-doped layered porous bayberry core-based activated carbon according to claim 1, characterized in that In step 2), the heating temperature is 70-100°C and the stirring reaction time is 4-6 h.

6. The method for preparing a highly nitrogen-doped layered porous bayberry core-based activated carbon according to claim 1, characterized in that In step 2), the potassium activator is one or both of KOH and KHCO3, preferably KHCO3.

7. The method for preparing a highly nitrogen-doped layered porous bayberry core-based activated carbon according to claim 1, characterized in that In step 3), the volume fraction of ammonia in the mixed atmosphere of nitrogen and ammonia is 30-70%, the calcination activation temperature is 600-1000° C., and the activation time is 2-4 h, preferably 2-3 h.

8. The method for preparing a highly nitrogen-doped layered porous bayberry core-based activated carbon according to claim 1, characterized in that In step 4), the concentration of the hydrochloric acid solution is 0.5-2 M, and stirring is performed during the soaking process. The soaking time is 20-60 minutes, and then the filtrate is washed with deionized water until the filtrate is neutral.

9. A highly nitrogen-doped hierarchical porous bayberry core-based activated carbon prepared by the method according to any one of claims 1 to 8.

10. The use of a highly nitrogen-doped layered porous bayberry core-based activated carbon as claimed in claim 9 for adsorbing and separating organic vapor in a CO2 atmosphere, characterized in that The organic vapor is one or more of ketones, aldehydes or acid compounds, preferably one or more of acetone, C1-C4 alkyl aldehydes, and C1-C4 alkyl acids.

Citation Information

Cited By

  • High-nitrogen-doped coconut shell activated carbon as well as preparation method and application thereof

    CN122276748A